Un asesinato literario : un caso critico - Gur, Batya, (Nuevos tiempos (Madrid, Spain), 2012)
Newly promoted Superintendent Ohayon must deal with the violent death of a famed critic and professor of literature at Hebrew University who is also one of Israel's most admired poets. Meanwhile, at around the same time although miles away, a bright, impassioned younger member of the same department dies in an apparent scuba-diving accident. Just as Ohayon had to master the intricacies of psychoanalysis as well as use his skills as a detective to solve his previous case, he now finds himself faced with profound intellectual and ethical dilemmmas about the relationship between the artist and his creation, with the complexities surrounding literary criticism and the thorny matter of plagiarism - and with a university department full of suspects. In his efforts to unravel the crime (or crimes), Michael Ohayon finds himself immersed in the cutthroat world of academia and confronted once again with issues of his own thwarted scholarly career. Bringing him into contact with Israel's intellectual elite, Literary Murder is both a sophisticated thriller and a revealing look at Israeli society and culture..